Financial development and poverty alleviation in Muslimdeveloping countries / Maizura Md Isa, Nor Hazila Ismail and Mohamed Eskandar Shah Mohd Rasid - Md Isa, Maizura; Ismail, Nor Hazila; Mohd Rasid, Mohamed Eskandar Shah (UiTM Cawangan Johor, 2018)
The positive impact of financial development on economic growth has been widely discussed, but the literature on the impact of financial development on poverty is inconclusive. Theoretical predictions advocate that financial development contributes directly to poverty reduction in three ways. Firstly, it alleviates poverty in a direct way via saving, insurance service and access to credit that can enhance the productivity of the poor. Secondly, financial development would enable the poor to access financial services, and enhance the productive assets of the poor, by improving productivity and increasing the potential to achieve sustainable gains. Lastly, the direct relationship between financial development and poverty reduction depends on the quality of financial instruments, services and institutions available to the poor. Varied explanatory discover on panel studies that suggest although financial development can foster economic growth, yet this does not could help in lighten the poorer people in Muslim developing countries.